Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acsami.0c12176
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Poly(vinyl alcohol) Nanocomposite Organohydrogel for Flexible Strain and Temperature Sensor

Abstract: Hydrogels are important for stretchable and wearable multifunctional sensors, but their application is limited by their low mechanical strength and poor long-term stability. Herein, a conductive organohydrogel with a 3D honeycomb structure was prepared by integrating carbon nanotubes (CNTs) and carbon black (CB) into a poly­(vinyl alcohol)/glycerol (PVA/Gly) organohydrogel. Such a nanocomposite organohydrogel is built on a physical cross-linking network formed by the hydrogen bonds among PVA, glycerol, and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
131
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 62 publications
2
131
0
Order By: Relevance
“…Besides, we observe that the organohydrogel‐based strain sensor could respond within 116 ms and recover within 68 ms (Figure 5c), which is faster than many other organohydrogel‐based strain sensors. [ 32,47–49 ]…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we observe that the organohydrogel‐based strain sensor could respond within 116 ms and recover within 68 ms (Figure 5c), which is faster than many other organohydrogel‐based strain sensors. [ 32,47–49 ]…”
Section: Resultsmentioning
confidence: 99%
“…This −0.0289°C −1 sensitivity value was found to be several times higher than previously reported values using other hydrogels displaying intrinsic conductivity and similar to those using hydrogels with ionic additives or volume changes (Table S1, Supporting Information). [11][12][13][14][15][16][17][18]24,25] The temperature sensor of TRH 1-1 showed a reversible change in resistance under temperature cycles with no significant hysteresis, as shown in Figure S9 (Supporting Information) (less than 1% change in resistance corresponding to each temperature during heating and cooling).…”
Section: Temperature Sensing Capabilities Of the Trhsmentioning
confidence: 99%
“…[10] Numerous previous works have been devoted to fabricating wearable temperature sensors based on hydrogels that can vary their electrical resistance as a result of changes in ion conductivity [11][12][13][14][15]24,25] or volume due to swelling/contraction with temperature. [16][17][18] Thermoresponsive hydrogels (TRHs) have played a crucial role in a variety of temperature-adaptive applications for actuators, [19] membranes, [20] displays, [21] and electrolytes [22] due to their intelligent thermo-responsive transitions. TRHs are classified by the two types of volume transition that they can undergo the lower critical solution temperature (LCST) or the upper critical solution temperature (UCST).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that the ion conductivity will be enhanced with the increase of temperature due to the increase of ion mobility. [204,205] Therefore, ionic hydrogels [33,119,[206][207][208] and ionogels [107,209] can also be designed into soft temperature sensors. For instance, Zhang et al [206] fabricated the dopamine-triggered gelation (DTG) conductive hydrogels, which exhibited unique thermoresponsive property.…”
Section: Temperature Sensorsmentioning
confidence: 99%